SYNTAX IN TIKTOK CAPTIONS: A STUDY OF SENTENCE FORMS AND FUNCTIONS - Salsabila, Sabrina; Tambunan, Nurul Fadilah; Andara, Nadhifa Shofi; Geovanni, Celli; Ismahani, Siti (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2026)
This study examines the syntactic forms and sentence functions found in TikTok captions as a representation of digital language communication. TikTok is a social media platform that integrates visual content and text, in which captions play a significant role in conveying meaning and interaction. This research employs a qualitative descriptive approach based on syntactic theories proposed by Chomsky, Givón, Halliday, O’Grady, and Aarts. The data consist of three English captions taken from the TikTok accounts @beaulinaa, @Rikey, and @lilly3ls. The findings reveal that TikTok captions predominantly use simple sentence structures with a high degree of ellipsis as a strategy of linguistic economy while maintaining acceptable grammatical patterns. In terms of function, the captions demonstrate pragmatic variation, including declarative, imperative, and expressive functions used for self-presentation, social relationship building, and audience engagement. These findings indicate that TikTok caption syntax represents a distinctive register of digital English that balances syntactic simplicity with communicative effectiveness in social media contexts. ABSTRAK Penelitian ini mengkaji bentuk sintaksis dan fungsi kalimat yang terdapat dalam caption TikTok sebagai representasi komunikasi bahasa digital. TikTok merupakan platform media sosial yang memadukan konten visual dan teks, di mana caption berperan penting dalam membangun makna dan interaksi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan landasan teori sintaksis dari Chomsky, Givón, Halliday, O’Grady, dan Aarts. Data penelitian berupa tiga caption berbahasa Inggris yang diambil dari akun TikTok @beaulinaa, @Rikey, dan @lilly3ls. Hasil analisis menunjukkan bahwa caption TikTok cenderung menggunakan kalimat sederhana dengan tingkat elipsis yang tinggi sebagai bentuk ekonomi bahasa, namun tetap mempertahankan struktur gramatikal yang dapat diterima. Dari segi fungsi, caption menampilkan keragaman fungsi pragmatik, seperti deklaratif, imperatif, dan ekspresif, yang digunakan untuk presentasi diri, pembentukan relasi sosial, serta peningkatan keterlibatan audiens. Temuan ini menunjukkan bahwa sintaksis caption TikTok membentuk ragam bahasa Inggris digital yang khas, yang menyeimbangkan kesederhanaan struktur sintaksis dengan efektivitas komunikasi dalam konteks media sosial.